Task-based Learning (TBL) in the Classroom for EFL Learners: How and Why? - Sholeh, Muhammad Badrus ((JELE) Journal Of English Language and Education, 2020)
In language teaching and learning, there are several methodologies and approaches; one of them is Task-Based Learning. Since the 1980s, this approach has had the most pedagogical attention in second language pedagogy. Task-based Learning is becoming increasingly common worldwide, particularly in English classes in Indonesia. The task's goal is to establish a clear reason for language use and create a natural meaning for language learning. The ideas and principles of Task-based Learning have proven to be effective in classrooms. This paper aims to explain why teachers should implement Task-Based Learning (TBL) in the language classroom and how to implement TBL during classroom instruction. The discussion begins with the introduction and the description of TBL. Then, it goes on TBL characteristics and continues with the approaches, the benefits, and framework of TBL.